Elizabeth Cady Stanton and Lucretia Mott: radical 'co-adjutors' in the American women's rights movement. Issue 2 (4th March 2021) - Vetter, Lisa Pace
ABSTRACT: Elizabeth Cady Stanton is widely considered to be the founder of the early women's rights movement in America. She convened the first convention dedicated specifically to women's rights in America, at Seneca Falls, New York, and she is credited with authoring the Declaration of Sentiments, arguably the founding document of the American women's rights movement. Stanton's unwavering insistence on women's enfranchisement drove much of her efforts. The History of Woman Suffrage (1881–1922), which Stanton initiated and coedited, is considered the definitive account of the early movement. For many commentators, the radicalism of Stanton's claims sets her apart from other reformers. However, I argue that another women's rights advocate, Lucretia Mott, is as radical as Stanton and, in some respects, perhaps more so. Mott held a comprehensive view of women's rights that included, but was not limited to, women's suffrage. Whereas Stanton sought to establish an organized reform movement and craft the official account of its origins, Mott resisted these efforts, instead preferring informal networks of activism and a more inclusive historical understanding. Whereas Stanton has been criticized for her elitist and racist views, Mott's lifelong commitment to abolitionism and human rights never wavered.